Request Strategies in Indonesian: An Analysis of Politeness Phenomena in Text Messages - -, Jeanyfer; Tanto, Trisnowati (Universitas Sanata Dharma, 2018)
A lot of linguists have paid a lot of attention to the phenomena of politeness—some said it should be in the area of Sociolinguistics, while others believe that it belongs to the domain of Pragmatics. The present study focuses on politeness phenomena as a part of Pragmatic domain as it aims to see how language, especially Indonesian, is used to realize politeness in text messages between people who would like to request a favor, thing, or information. It is believed that speakers use different strategies to achieve their goals when talking to different people. The study utilizes Brown’s and Levinson’s theory on politeness strategies to examine the strategies used by the speaker when communicating with hearer of different power and distance relations. Along with the theory, this study also employs request strategies that are derived from Searle’s speech act classifications. The result shows that in terms of strategies, people have the tendency to use negative politeness strategies in communicating with other people that have more power than them, while a mix between negative and positive strategies are used mostly to those they consider peer or lower in power.Keywords: politeness strategies, request strategies, speech acts, pragmatics